Accuracy and Precision of Alchemical Relative Free Energy Predictions with and without Replica‐Exchange. Issue 1 (27th November 2019) - Wan, Shunzhou; Tresadern, Gary; Pérez‐Benito, Laura; van Vlijmen, Herman; Coveney, Peter V.
Abstract: A systematic and statistically robust protocol is applied for the evaluation of free energy calculations with and without replica‐exchange. The protocol is based on ensemble averaging to generate accurate assessments of the uncertainties in the predictions. Comparison is made between FEP+ and TIES—free energy perturbation and thermodynamic integration with enhanced sampling—the latter with and without the so‐called "enhanced sampling" based on replica‐exchange protocols. Standard TIES performs best for a reference set of targets and compounds; no benefits accrue from replica‐exchange methods. Evaluation of FEP+ and TIES with REST—replica‐exchange with solute tempering—reveals a systematic and significant underestimation of free energy differences in FEP+, which becomes increasingly large for long duration simulations, is confirmed by extensive analysis of previous publications, and raises a number of questions pertaining to the accuracy of the predictions with the REST technique not hitherto discussed. Abstract : A comparison between the TIES and FEP+ alchemical free energy methods for calculating relative free energies of binding of ligands to a target protein is reported. TIES is found to perform best. Replica‐exchange methods exhibit artefactual reduction in these free energy differences, the FEP+ predictions degrading increasingly with longer simulation time.